Tumor Necrosis Factor (TNF) α, Endothelin (ET) 1 and α1-Acid Glycoprotein (AGP) as Potential Urine and Serum Markers of Metabolic Complications in Psoriasis? - Julia Nowowiejska; Anna Baran; Justyna M. Hermanowicz; Beata Sieklucka; Dariusz Pawlak; Iwona Flisiak (Adis, Springer Healthcare, 2023)
Abstract Introduction Psoriasis, one of the most frequent dermatoses, strongly associated with metabolic disorders which increase patients' comorbidity and mortality. Hence, it is essential to look for markers of such complications. Our aim was to assess the clinical utility of urinary tumor necrosis factor alpha (TNFα), endothelin 1 (ET-1) and α1-acid glycoprotein (α1AGP) as well as their serum concentrations as markers of metabolic complications in psoriatics, and to examine the relations of these markers to clinical and demographic parameters. Methods The study involved 60 patients with plaque psoriasis and 30 volunteers without skin diseases (the control group). Serum and urinary concentrations of TNFα, ET-1 and α1AGP were measured by ELISA. Psoriasis severity was assessed using the psoriasis activity and severity index (PASI). Routine laboratory investigations were additionally performed. Results All serum markers were significantly higher in the patients compared to the controls. TNFα was undetectable in the urine in half of the patients. The urinary ET-1/creatinine concentration ratio was significantly lower in the psoriatics than the controls, whereas the absolute urinary α1AGP was significantly higher and the α1AGP/creatinine ratio was insignificantly different. There was no correlation between serum or urinary markers and PASI. All serum markers were higher in patients with psoriasis lasting less than 15 years. Conclusions Serum TNFα, ET-1 and α1AGP seem to be useful biomarkers of metabolic syndrome in psoriatics. ET-1 could perhaps become a urinary marker of metabolic disorders in psoriatics, but further studies are required to confirm that a decreased ET-1 concentration in urine is a reliable predictive tool. Increased urinary α1AGP also requires more in-depth research as a potential marker. TNFα urine assessment does not seem to be useful for screening for metabolic disorders in psoriatics. Serum or urinary TNFα, ET-1 and α1AGP do not seem to be associated with psoriasis severity or duration.